2012
DOI: 10.1098/rspb.2012.0113
|View full text |Cite
|
Sign up to set email alerts
|

Close kinship within multiple-genotype malaria parasite infections

Abstract: Malaria infections containing multiple parasite genotypes are ubiquitous in nature, and play a central role in models of recombination, intra-host dynamics, virulence, sex ratio, immunity and drug resistance evolution in Plasmodium. While these multiple infections (MIs) are often assumed to result from superinfection (bites from multiple infected mosquitoes), we know remarkably little about their composition or generation. We isolated 336 parasite clones from eight patients from Malawi (high transmission) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
135
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 50 publications
(74 reference statements)
11
135
1
Order By: Relevance
“…It has been well established that both clinical and subclinical T. orientalis infections frequently occur as a mixture of genotypes (Bogema et al, 2015;Eamens et al, 2013b;Kamau et al, 2011;Ota et al, 2009;Sivakumar et al, 2014), a phenomenon characteristic of apicomplexan parasites (Nkhoma et al, 2012;Katzer et al, 2006). While the Ikeda genotype of T. orientalis has been clearly associated with clinical outbreaks of disease, in Australian herds it has been demonstrated to co-occur with the Chitose genotype with high frequency (Eamens et al, 2013c) in the presence or absence of benign genotypes (Buffeli and Type 5) (Eamens et al, 2013c;Perera et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been well established that both clinical and subclinical T. orientalis infections frequently occur as a mixture of genotypes (Bogema et al, 2015;Eamens et al, 2013b;Kamau et al, 2011;Ota et al, 2009;Sivakumar et al, 2014), a phenomenon characteristic of apicomplexan parasites (Nkhoma et al, 2012;Katzer et al, 2006). While the Ikeda genotype of T. orientalis has been clearly associated with clinical outbreaks of disease, in Australian herds it has been demonstrated to co-occur with the Chitose genotype with high frequency (Eamens et al, 2013c) in the presence or absence of benign genotypes (Buffeli and Type 5) (Eamens et al, 2013c;Perera et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…It was not established whether these mixed infections arose from successive inoculations of distinct parasite populations from multiple tick bites, or transmission of multiple sporozoite genotypes from individual ticks. However, evidence from field studies of mosquito transmission of the malaria parasite, Plasmodium falciparum (Nkhoma et al, 2012), suggest that genetic recombination within the insect vector is sufficient to generate a genetically diverse population of sporozoites. Indeed, recombination within the vector is believed to be the major source of genetic diversity in P. falciparum, rather than ''superinfection'' from multiple mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,36 The transmission of multiple gametocyte clones at one time has been shown in P. falciparum and is expected to be an important contributor to MOI in areas of low transmission. [37][38][39] Because increased MOI facilitates recombination, these forces could allow P. vivax to maintain high genetic diversity despite lower levels of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of three major WGA kits (PicoPLEX/REPLI-g Midi/Mini) showed that each performs with comparable accuracy. Accuracy was further increased by collating the results of replicate genotyping runs and removing cells with more than five mixed genotype calls (as in Nkhoma et al 2012). These were considered situations in which the WGA product contained more than one parasite genome.…”
Section: High-throughput Capture Of Parasite-infected Rbcsmentioning
confidence: 99%
“…Although diversity at individual loci provides a minimum estimate of genotypes present, the actual numbers of genotypes present, and their relationships and relative abundance within infections cannot currently be determined. Furthermore, most malaria species cannot be maintained in a long-term culture (e.g., P. vivax [Noulin et al 2013], P. ovale, and P. malariae), precluding dilution cloning of component parasites, and this approach is extraordinarily cumbersome even for readily cultivable species such as P. falciparum (e.g., Rosario 1981;Nkhoma et al 2012). …”
mentioning
confidence: 99%